2015
DOI: 10.1080/09658211.2015.1098705
|View full text |Cite
|
Sign up to set email alerts
|

“Blind” interviewing: Is ignorance bliss?

Abstract: Aspen Systems Corporation, particularly Gayle Garmise and Erica Pope, provided tireless work on editing and re-editing the various drafts of the Guide. CSR, Incorporated, provided support in arranging the group's many meetings. Staff from NIJ and the Office of Justice Programs provided valuable input, particularly Janice Munsterman, Karl Bickel, Luke Galant, and Anjali Swienton. Special thanks are extended to Lisa Forman and Kathleen Higgins for their contributions to the TWG program and to Lisa Kaas for her p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 23 publications
4
30
0
1
Order By: Relevance
“…Although forensic interviewers in our sample predominantly reported using an informed interviewing approach, approximately one‐quarter of interviewers reported using a blind approach in at least some of their forensic interviews. This is particularly surprising given the lack of empirical research on the effectiveness of this technique (but see Cantlon et al, ; Rivard et al, ). Importantly, when assessing real‐world interviewers' opinions about blind interviewing, it is clear that a sizeable portion of the present sample strongly objects to the idea of blind interviewing, not providing any advantage of the technique when asked, with close to a third being unwilling to conduct blind interviews under any circumstance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although forensic interviewers in our sample predominantly reported using an informed interviewing approach, approximately one‐quarter of interviewers reported using a blind approach in at least some of their forensic interviews. This is particularly surprising given the lack of empirical research on the effectiveness of this technique (but see Cantlon et al, ; Rivard et al, ). Importantly, when assessing real‐world interviewers' opinions about blind interviewing, it is clear that a sizeable portion of the present sample strongly objects to the idea of blind interviewing, not providing any advantage of the technique when asked, with close to a third being unwilling to conduct blind interviews under any circumstance.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a laboratory study using adult witnesses to a mock‐crime by Rivard, Pena, and Schreiber Compo () revealed that student interviewers with no pre‐interview knowledge of the crime gathered more accurate details from witnesses than those who read a brief, correct summary of the crime, but not significantly more than those who had incorrect pre‐interview information. Blind interviewers were more likely to begin the interview with a non‐suggestive question than were their informed counterparts and were also able to recall more details about the interview when asked to write a summary of the witness's account.…”
Section: Current Forensic Interview Protocolsmentioning
confidence: 99%
“…A potential limitation to the application of this research is that we employed a procedure with no widespread use in a forensic scenario. Multiple-choice questions may not be the preferred option during a forensic interview, although Rivard, Pena and Schreiber Compo (2015) found 8% of multiple-choice questions during an interview, suggesting that they are not completely out of place in that context. While our procedure guaranteed the necessary experimental control and comparability with previous studies, future research on this topic should search for ways to improve its ecological validity and the generalization of the findings.…”
Section: Discussionmentioning
confidence: 94%
“…Um aprofundamento em como obter descrições do rosto do criminoso foge do escopo deste artigo, cabe apontar que devem ser priorizadas perguntas abertas (e.g., você falou que o rosto dele era um pouco diferente, poderia me falar mais sobre isso? ; Milne, Shaw & Bull, 2007;Rivard, Pena & Compo, 2016). Perguntas fechadas ou sugestivas (e.g., você tem certeza que ele não tinha uma cicatriz?)…”
Section: Continuarunclassified